2012
DOI: 10.1017/jfm.2012.454
|View full text |Cite
|
Sign up to set email alerts
|

Stokes flow singularity at the junction between impermeable and porous walls

Abstract: For two-dimensional, creeping flow in a half-plane, we consider the singularity that arises at an abrupt transition in permeability from zero to a finite value along the wall, where the pressure is coupled to the seepage flux by Darcy’s law. This problem represents the junction between the impermeable wall of the inflow section and the porous membrane further downstream in a spiral-wound desalination module. On a macroscopic, outer length scale the singularity appears like a jump discontinuity in normal veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 111 publications
(177 reference statements)
0
28
0
Order By: Relevance
“…Based upon the following characteristic scales, Characteristic length: The case Θ = π/2 applies to a solid spacer adjoining the membrane, and represents one of the problems treated in this paper. The abrupt end of the sealed, entry section of the lower wall corresponds to Θ = π , and was treated by Nitsche and Parthasarathi [8]. The singular points are indicated with large, closed circles…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Based upon the following characteristic scales, Characteristic length: The case Θ = π/2 applies to a solid spacer adjoining the membrane, and represents one of the problems treated in this paper. The abrupt end of the sealed, entry section of the lower wall corresponds to Θ = π , and was treated by Nitsche and Parthasarathi [8]. The singular points are indicated with large, closed circles…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Satisfaction of both no-slip and no-shear means that the slip condition (9) is then also satisfied exactly for any value of the slip length σ . Nitsche and Parthasarathi [8] found this degeneracy to propagate beyond the leading outer solution through second order in both inner and outer asymptotic expansions, and concluded that slip does not play a role for the case of a flat abutment of porous and solid walls. The case Θ = π is now seen to be fluke: for any other wedge angle Θ, the shear stress (19) is inconsistent with the radial velocity component (16) in Eq.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations